2021
DOI: 10.3390/jcm10051033
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Integrated Genetic Information on Diagnosis and Prognostication for Myeloproliferative Neoplasms in the Next-Generation Sequencing Era

Abstract: Since next-generation sequencing has been widely used in clinical laboratories, the diagnosis and risk stratification of hematologic malignancies are greatly dependent on genetic aberrations. In this study, we analyzed the genomic landscapes of 200 patients with myeloproliferative neoplasms (MPNs) and evaluated the impact of the genomic landscape on diagnosis and risk stratification. Mutations in JAK2, CALR and MPL were detected in 76.4% of MPNs. The proportion of patients with clonal genetic markers increased… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…DNA samples from peripheral blood or bone marrow at diagnosis were used. Mutation data was obtained using targeted NGS panels as previously described (10,11). We used two versions of the NGS panel depending on the accessed time points.…”
Section: Genomic Datamentioning
confidence: 99%
“…DNA samples from peripheral blood or bone marrow at diagnosis were used. Mutation data was obtained using targeted NGS panels as previously described (10,11). We used two versions of the NGS panel depending on the accessed time points.…”
Section: Genomic Datamentioning
confidence: 99%
“…Unlike what happens in MDS, in MPNs the SF3B1 mutations appear to increase the risk of fibrotic transformation [33,34]. It has also been suggested that the co-occurrence of SF3B1 and JAK2 or MPL mutations is associated with an increased risk of thrombotic events [35,36].…”
Section: Sf3b1 In Myeloproliferative Neoplasmsmentioning
confidence: 99%
“…The incidence of essential thrombocytosis in newborn infants is not well known. Essential thrombocytosis is represented by megakaryocytic hyperplasia in the bone marrow with thrombocytosis, which is mainly caused by mutations in Janus kinase 2 ( JAK2 ) or myeloproliferative leukemia ( MPL , a TPO receptor gene) [ 27 ]. It is known to increase the risk of vascular events such as hemorrhage and thrombosis due to thrombocytosis.…”
Section: Classification Of Thrombocytosismentioning
confidence: 99%